2016
DOI: 10.3389/fgene.2016.00085
|View full text |Cite
|
Sign up to set email alerts
|

TP53 Mutation Spectrum in Smokers and Never Smoking Lung Cancer Patients

Abstract: Background: TP53 mutations are among the most common mutations found in lung cancers, identified as an independent prognostic factor in many types of cancers. The purpose of this study was to investigate the frequency and prognostic impact of TP53 mutations in never-smokers and in different histological subtypes of lung cancer.Methods: We analyzed tumor tissue from 394 non-small cell carcinomas including adenocarcinomas (n = 229), squamous cell carcinomas (n = 112), large cell carcinomas (n = 30), and others (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 31 publications
8
82
1
Order By: Relevance
“…Although previous studies revealed that the number of TP53 mutations are common in noncancerous tissue and accumulate with age and tobacco consumption, we detected an overall higher rate of TP53 mutations in younger patients particularly in <50 and 50–60 age groups. TP53 mutations showed a strong enrichment of smoking related SI4 and aflatoxin related SI24, both constituted of C>A transversions, indicating guanine damages that are being repaired by transcription‐coupled nucleotide excision repair.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Although previous studies revealed that the number of TP53 mutations are common in noncancerous tissue and accumulate with age and tobacco consumption, we detected an overall higher rate of TP53 mutations in younger patients particularly in <50 and 50–60 age groups. TP53 mutations showed a strong enrichment of smoking related SI4 and aflatoxin related SI24, both constituted of C>A transversions, indicating guanine damages that are being repaired by transcription‐coupled nucleotide excision repair.…”
Section: Discussioncontrasting
confidence: 93%
“…Considering the crucial roles of p53 in maintaining genome stability, the loss or disruption of p53 function can lead to uncontrolled cell proliferation and cancer . Past studies demonstrated that the frequency of TP53 mutations increased with tobacco consumption . Therefore, the relation between TP53 mutations, tobacco consumption and patient age remains an open question.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tobacco smoke contains many carcinogenic components that damage DNA and increase the overall rate of mutation, affect methylation patterns and modify gene expression profiles, all of which affect the risk of cancer initiation and progression. An example of a gene affected by smoking is P53 with almost twice the mutation rate in smokers vs. never-smokers 2 . Chemical features of nicotine and other compounds in tobacco smoke result in a specific DNA mutation signature in cancer patients smoking tobacco 3 and analysis of the effects of smoking on cancer historically focused on defining and understanding the molecular mechanisms of such signatures.…”
Section: Mainmentioning
confidence: 99%
“…TP53 mutations are common, present in approximately 50% of lung cancers, and are prognostic of poor outcomes 6,85 . Mutations in this gene deactivate the G1 cell-cycle checkpoint 6 .…”
Section: Tp53 Mutationsmentioning
confidence: 99%